Palgrave Handbook of Critical Posthumanism
36 illus., 30 illus. in color. eReference.
Keywords: Palgrave Handbook of Critical Posthumanism is a major reference work on the paradigm emerging from the challenges to humanism, humanity, and the human posed by the erosion of the traditional demarcations between the human and nonhuman. This handbook surveys and speculates on the ways in which the posthumanist paradigm emerged, transformed, and might further develop across the humanities. With its focus on the posthuman as a figure, on posthumanism as a social discourse, and on posthumanisation as an on-going historical and ontological process, the volume highlights the relationship between the humanities and sciences. The essays engage with posthumanism in connection with subfields like the environmental humanities, health humanities, animal studies, and disability studies. The book also traces the historical representations and understanding of posthumanism across time. Additionally, the contributions address genre and forms such as autobiography, games, art, film, museums, andtopics such as climate change, speciesism, anthropocentrism, and biopolitics to name a few. This handbook considers posthumanism’s impact across disciplines and areas of study. .